Body weight and eating behaviour of Nigerian postgraduate students in UniSZA, Malaysia - Abubakar, HA; Shahril, MR; Wafa, SW (2015)
University is a critical period where unhealthy change in eating behaviour develops, notably among international students. Therefore, the aim for this study is to investigate the change in body weight and eating behaviour of Nigerian postgraduate students in Universiti Sultan Zainal Abidin (UniSZA), Malaysia. It was hypothesized that, after six months living in Malaysia, the body weight and eating behaviour will not change. A total of 108 students completed a set of self administered questionnaire, and their weight and height was measured on arrival in Malaysia and after six months of stay. Descriptive statistic and paired t-test was carried out to analyze the data (SPSS Version 20). The study shows that, body weight was statistically increased by 2.3 ± 0.5kg. Intake of fat (p=0.006), sodium (p=0.012) and iron (p<0.001) was significantly reduced, while intake of vitamin c increased (p=0.004) after six months. There is also a decline in the frequency of having breakfast, lunch, dinner every day. Intake of fruits and vegetables everyday was also reduced. Meal skipping frequency has slightly increased, with breakfast as the most frequent skipped meal compared at the time of arrival in Malaysia. . As a conclusion, the students might have gained weight by changing their eating behaviors due to the new environment in Malaysia. There is a need to develop awareness program on nutrition that could encourage and promote healthier eating behavior and lifestyle in adapting new environment for international students.